Formulation of Chemically Defined Media and Growth Evaluation of Ligilactobacillus salivarius ZJ614 and Limosilactobacillus reuteri ZJ625 - Kwoji, Iliya Dauda; Okpeku, Moses; Adeleke, Matthew Adekunle; Aiyegoro, Olayinka Ayobami (Frontiers in Microbiology, 2022)
Lactic acid bacteria are increasingly becoming important dietary supplements due to their health benefits when consumed in adequate quantity. The increasing attention on these important microbes has necessitated an in-depth understanding of their physiological processes, such as nutritional requirements and growth patterns, to better harness their probiotic potentials. This study was carried out to determine the nutrient requirements for the growth of L. salivarius ZJ614 and L. reuteri ZJ625 from a chemically defined medium and evaluate growth kinetics by fitting different sigmoidal growth models. The complete CDM contains 49 nutritional ingredients: glucose, Tween-80®, mineral salts, buffers, amino acids, vitamins, and nucleotides at defined concentrations. Additionally, the minimum nutritional requirements of the isolates were determined in a series of single-omission experiments (SOE) to compose the MDM. Growth curve data were generated by culturing in an automated 96-well micro-plate reader at 37 ℃ for 36 hours and photometric readings (optical density: OD600). The data were summarized in tables and charts using Microsoft Excel, while growth evaluation was carried out using open-source software (Curveball) on Python. The results revealed that omission of the amino acids, vitamins and nucleotides groups resulted in 2.0%, 20.17% and 60.24% (for L. salivarius ZJ614), and 0.95%, 42.7% and 70.5% (L. reuteri ZJ625) relative growths, respectively. Elimination of the individual CDM components also indicates varying levels of growth by the strains. The growth curve data revealed Logisticlag2 and Baranyi-Roberts models as the best fits for L. reuteri ZJ625 and L. salivarius ZJ614, respectively. All the strains grew optimally on the CDM and MDM and compared auspiciously to de-Man Rogosa Sharpe (MRS) broth. We also described the growth kinetics of these isolates in the CDM, and the best models revealed the estimated growth parameters for each of these isolates.